مفهوم النص في التراث العربي: خطوة في تكامل المنهج النقلي والعقلي - Abdullah, A.; Al-Obaidi, Z. (Universiti Sains Islam Malaysia, 2024)
Over one thousand years ago, the ancient Arab grammarians expressed their interest in Arabic Grammar and Morphology; their studies were concentrated on words and sentences. Therefore the Sentence remained in a high position at the Language Studies. The main objective is to investigate the Arab heritage knewledge on texts semantically according to coherent and cohesion terms along with its special features at text level. Adoption of descriptive analytical approach, the findings revealed that: the text has its roots in the history of Arabic rhetoric; the ancient Arab scholars were on a great deal of precision in dealing with text' linguistic issues, when they understood the phenomenon of language comprehension and its laws. This is an indication that the approach adopted by the University in the integration of heritage sciences and contemporary sciences is highly significant.